2010
DOI: 10.1139/l09-175
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic jump in sloping channels: roller length and energy loss

Abstract: This paper deals with the roller length and energy loss of a large variety of hydraulic jumps in horizontal and sloping channels. The supercritical upstream flow originated from a standard ogee weir. A stilling basin with bottom slopes of 0.0, -0.025, -0.050, -0.075, and -0.100 was used to generate the jumps. Based on the energy principle, a semiempirical method to predict the roller length is presented. Predictions based on the proposed method agree well with the results reported by the authors and other rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 6 publications
2
10
0
1
Order By: Relevance
“…On the other hand, results obtained with the method of [16] fail to account for the different apron slopes. Results obtained by method [19] adequately follow the trend of measured values. However, they are very scattered, with relative errors between −17% and +34%.…”
Section: Roller Lengthsupporting
confidence: 67%
See 3 more Smart Citations
“…On the other hand, results obtained with the method of [16] fail to account for the different apron slopes. Results obtained by method [19] adequately follow the trend of measured values. However, they are very scattered, with relative errors between −17% and +34%.…”
Section: Roller Lengthsupporting
confidence: 67%
“…However, they are very scattered, with relative errors between −17% and +34%. Results obtained by [19] fail to account for different positions of the hydraulic jump. We hypothesize for methods [16,19] that the observed disagreements exist due to differences in experimental setups, the sensitivity of their equations, and their coefficients being problem dependent.…”
Section: Roller Lengthmentioning
confidence: 98%
See 2 more Smart Citations
“…It was found that the negative slope of the basin reduced the sequent depth ratio, whereas a positive slope increased the sequent ratio. Also, Beirami and Chamani (2010) reported that the energy loss in the classical jump is greater than that in any jump forming on negative or positive slopes. Hartner et al (2003) stated that the characteristics of the hydraulic jump depend on Froude number (F r1 ).…”
Section: Introductionmentioning
confidence: 99%